Exploring rice tolerance to salinity and drought stresses through Piriformospora indica inoculation: understanding physiological and metabolic adaptations - Raeisi Vanani, Ali; Sheikhi Shahrivar, Fatemeh; Nouri, Amin; Sepehri, Mozhgan (Frontiers in Plant Science, 2024)
Drought and salinity are significant challenges to global food security. This study investigated the interactive impacts of Piriformospora indica inoculation with salinity and drought stresses on rice. Two greenhouse experiments were conducted. The first experiment evaluated two P. indica inoculation levels and three salinity levels (0-, 50-, and 100-mM sodium chloride), while the subsequent experiment assessed two inoculation levels under three drought intensities (25%, 50%, and 100% of available water content). P. indica spores were inoculated following optimized seed disinfection and germination processes. The shoot and root biomass under salinity stress were consistently higher in inoculated plants compared to controls. Sodium concentrations in shoots and roots exhibited an overall upward trend, with the trend being less pronounced in inoculated plants due to increased potassium uptake. Under salinity stress, nitrogen, magnesium, and calcium concentrations significantly increased in inoculated plants. With increasing salinity, there was a significant increase in catalase enzyme activity and soluble carbohydrate concentrations across all treatments, with a greater increase in inoculated plants. Plants under drought stress experienced reduced root and shoot biomass, but inoculated plants maintained higher biomass. Increasing drought stress led to decreased nitrogen, magnesium, and calcium concentrations in all treatments, with the reduction being less severe in inoculated plants. Catalase enzyme activity and carbohydrate increased with rising drought stress, with the increase being more pronounced in inoculated plants compared to non-inoculated ones. By promoting plant growth, nutrient uptake, and stress tolerance, P. indica inoculation has a significant potential to enhance crop productivity in extreme climate conditions. Abbreviations: Completely Randomized Design (CRD), Available Water Content (AWC), Field Capacity (FC). Permanent Wilting Point (PWP), Arbuscular Mycorrhizal Fungi (AMF)